2020
DOI: 10.31592/aeusbed.804853
|View full text |Cite
|
Sign up to set email alerts
|

Velilerin Okul Öncesi Eğitim Hakkında Görüşlerinin İncelenmesi

Abstract: Bu araştırmada çocuklarını okul öncesi eğitim kurumlarına gönderen ebeveynlerin okul öncesi eğitim hakkında düşünceleri araştırılmıştır. Bu doğrultuda, velilere göre okul öncesi eğitimin ne olduğu, velilerin çocuklarını okul öncesi eğitim kurumlarına gönderme nedenleri, okul öncesi eğitimde yapılan uygulamalardan memnuniyetleri ile velilerin okul öncesi eğitime yönelik istek ve önerileri incelenmiştir. Araştırmaya 7'si kadın 4'ü erkek 11 veli katılmıştır. Katılımcılarla 15 sorudan oluşan yarı yapılandırılmış g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
4
0
3
Order By: Relevance
“…On the other hand, Bay, Bahçıvan, and Kalay (2018) underlined parents' demands for more social activities. Various studies also reported how parents emphasized activities that included peer interaction supporting social skills as positive outcomes of early childhood education (Konca, 2020;Sak, Şahin-Sak, Öneren-Şendil, & Taşkın, 2020). In a parallel manner, Ceylan (2019) underlined that social activities that schools offer can even influence parents' choice of school.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Bay, Bahçıvan, and Kalay (2018) underlined parents' demands for more social activities. Various studies also reported how parents emphasized activities that included peer interaction supporting social skills as positive outcomes of early childhood education (Konca, 2020;Sak, Şahin-Sak, Öneren-Şendil, & Taşkın, 2020). In a parallel manner, Ceylan (2019) underlined that social activities that schools offer can even influence parents' choice of school.…”
Section: Discussionmentioning
confidence: 99%
“…"Eğitim ortamının materyal yönünden zengin, aktif katılımın sağlandığı ve çocuk merkezli olmasıdır" (Konca, 2020).…”
Section: Yöntem Araştırmanın Modeliunclassified
“…For this reason, the age range of early childhood education will be given as 0-6 years in this article. "Early childhood education" is defined as "all kinds of educational activities that enable the development of children between the ages of 0-6 and are carried out in a systematic and planned manner, for most parents, where their children share responsibilities with a non-family member for the first time, and where parents encounter experiences they have never had before" (Gullo & Hughes, 2011;Konca, 2020;Topaç et al, 2012). Early childhood education aims to support the mental, physical, social, and emotional development of children and to enable them to acquire good habits, create a common growing area for children from unfavorable environmental and family conditions, and prepare them for primary school (Milli Eğitim Kanunu, 2013).…”
Section: Early Childhood Educationmentioning
confidence: 99%